2020
DOI: 10.3389/fgene.2020.00131
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Landscape of Dystrophin Mutations in Italy: A Nationwide Study

Abstract: in 57%, duplications in 11% and small mutations in 32%. In BMD, we found deletions in 78%, duplications in 9% and small mutations in 13%. In BMD, there are a higher number of deletions, and small mutations are more frequent than duplications. Among small mutations that are generally frequent in both phenotypes, 44% of DMD and 36% of BMD are nonsense, thus, eligible for stop codon read-through therapy; 63% of all out-of-frame deletions are eligible for single exon skipping. Patients were also assigned to Italia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 55 publications
1
65
0
2
Order By: Relevance
“…We may firstly consider that some DMD mutations may have escaped MLPA and sequencing testing, as for atypical mutations occurring in regulatory regions or due to deep intronic variants/rearrangements. 20 Because these are estimated to be less than 1% in various patient series, 21 , 22 , 23 , 24 their impact on the detection rate should be low, and only a few cases might have been missed. Ethnicity may also play a role in mutation type frequency, as already described 23 ; only the adoption of a single and fully accurate method able to detect all mutation types, such as whole-genome sequencing (WGS), will allow us to unravel these events and their frequency in the various populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We may firstly consider that some DMD mutations may have escaped MLPA and sequencing testing, as for atypical mutations occurring in regulatory regions or due to deep intronic variants/rearrangements. 20 Because these are estimated to be less than 1% in various patient series, 21 , 22 , 23 , 24 their impact on the detection rate should be low, and only a few cases might have been missed. Ethnicity may also play a role in mutation type frequency, as already described 23 ; only the adoption of a single and fully accurate method able to detect all mutation types, such as whole-genome sequencing (WGS), will allow us to unravel these events and their frequency in the various populations.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Because these are estimated to be less than 1% in various patient series, 21 , 22 , 23 , 24 their impact on the detection rate should be low, and only a few cases might have been missed. Ethnicity may also play a role in mutation type frequency, as already described 23 ; only the adoption of a single and fully accurate method able to detect all mutation types, such as whole-genome sequencing (WGS), will allow us to unravel these events and their frequency in the various populations. 25 Second, a few patients referred as DMD/BMD or generally as possible dystrophinopathies may represent phenocopies of other clinical entities like limb-girdle muscular dystrophies (LGMDs) or other rare hereditary myopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis of DMD patients showed that large deletions are the most common type of mutations worldwide (64% in Oceania, 66% in Europe, 70% in Americas, 72% in Asia, and 88% in Africa). Population-based cohort studies (Chinese [ 16 ], Spanish [ 17 ], and Italian [ 18 ]) also manifested racial characteristics of DMD mutation types.…”
Section: Genetic Pathogenesis Of Dmdmentioning
confidence: 99%
“…On the other hand, if a portion of mRNA skips the exon with a mutation, a smaller protein could still be produced on the condition that the skipped exon is in-frame. Previous works hypothesized that mutations in in-frame exons might cause milder phenotypes via spontaneous exon skipping of the mutated exon, which may weaken the mutation consequence [14,37]. This favorable precondition is the rule for most central dystrophin exons: all of them between 23 and 42 are in-frame.…”
Section: Plos Onementioning
confidence: 99%
“…The first nonsense variants and other small defects were only identified six years after the DMD gene cloning [12,13]. Unlike most disease genes, single nucleotide substitutions and small insertion/deletion of bases are a less frequent cause of disease [14,15]. Random nonsense mutations were found in 10-15% of DMD cases [16].…”
Section: Introductionmentioning
confidence: 99%